The Anti-Roma Europe: Modern ways of disciplining the Roma body in urban spaces / A Europa Anti-Roma: Formas modernas de disciplina do corpo Roma nos espaços urbanos - Fejzula, Sebijan (Revista Direito e Práxis, 2019)
DOI: 10.1590/2179-8966/2019/43882 Abstract This article examines the challenges of conceptualizing the experiences of Roma people in an Anti-Roma Europe within a domain of what has been defined as human rights, internal security and “integration” policies. This paper focuses on the politics of structural and everyday Anti-Roma racism and its traumatic effects on the Roma people in Europe. I engage with Philomena Essed’s definition of the concept of everyday racism as practices, activities and attitudes accepted in a given system. The notion of structural racism refers to racialized governmentalities and ideologies/epistemologies that reproduce power relations that are grounded on white privilege/supremacy. Accordingly, racism reproduce dehumanizationfor the maintenance of whiteness as state sovereignty. Keywords: Permanent state of exception; Structural racism: Everyday Antigypsyism. Resumo Este artigo examina os desafios de conceptualizar as experiências dos povos Roma numa Europa Anti-Roma no enquadramento dos direitos humanos, a segurança interna e as políticas de "integração”. O artigo foca-se na política de racismo quotidiano anti-roma e o racismo estrutural e os seus efeitos traumáticos na população Roma na Europa. Utiliza-se a definição de “racismo quotidiano” de Philomena Essed, enquanto práticas, atividades e atitudes rotineiras que são aceites num dado sistema. A noção de racismo estrutural refere-se a governabilidades racializadas e ideologias/epistemologias que reproduzem relações de poder assentes no privilégio/supremacia branca. Neste sentido, o racismo reproduz a desumanização para a manutenção da branquitude como fundamento da soberania do estado. Palavras-chave: Estado permanente de exceção; racismo estrutural; anticiganismo quotidiano.